Digital-Based Entrepreneurship Development, Investment Socialization and Marketing of Asipa Micro, Small And Medium Enterprises In South Tangerang City, Banten - Sri Yulianti; Ani Nuraini; Titus Indrajaya; Maya Sova; Sakti Brata Ismaya; Rushadiyati Rushadiyati (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
This service examines the development of entrepreneurship in the new normal period through training, with steps that can be taken to empower business actors in the development of ASIPA MSMEs in South Tangerang City. Training methods using offline and online media. While this service is an effort to socialize investment and marketing for micro, small and medium enterprises at the Creative Industries and Business Actors Association (ASIPA) based on digitalization by participating in training, marketing, obtaining tips for successfully investing in the Indonesia Stock Exchange (IDX) and financially investing in shares (PT. NH Korindo). This training conducts interactive coaching and socialization about the ease of doing business for MSME actors from participants of the Creative Industries and Business Actors Association (ASIPA) is always active in government programs to support income increase for MSME entrepreneurs consistently marketing through social media; Online stores, marketplaces, booths in malls, bazaars, and on websites to optimize facilities and keep up with the times. Thus, the Social Piety Index will form economic development in the community of Serua Village, Ciputat District, South Tangerang City, Banten.